2015
DOI: 10.1055/s-0035-1565083
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Alternative Administration Routes of Melatonin: A Systematic Review

Abstract: Background: Melatonin is traditionally administered orally but has a poor and variable bioavailability. This study aims to present an overview of studies investigating the pharmacokinetics of alternative administration routes of melatonin. Methods: A systematic literature search was performed and included experimental or clinical studies, investigating pharmacokinetics of alternative administration routes of melatonin in vivo. Alternative administration routes were defined as all administration routes except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 25 publications
(30 reference statements)
0
47
0
3
Order By: Relevance
“…In contrast, intravenous MLT administration every 2 hours induced a sustained increase in circulating MLT concentrations >600‐fold, and a further 2‐fold increase in the cerebral cortex compared with patch administration. In adult studies, the maximum concentrations of MLT are reached with transdermal patches between 1 and 18 hours following application . These human studies observed inconsistent concentrations of MLT between patches; generally, the higher dose patches showed a faster time to maximum concentration, for example 20‐100 mg patches produced a peak circulation at 1‐2 hours .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, intravenous MLT administration every 2 hours induced a sustained increase in circulating MLT concentrations >600‐fold, and a further 2‐fold increase in the cerebral cortex compared with patch administration. In adult studies, the maximum concentrations of MLT are reached with transdermal patches between 1 and 18 hours following application . These human studies observed inconsistent concentrations of MLT between patches; generally, the higher dose patches showed a faster time to maximum concentration, for example 20‐100 mg patches produced a peak circulation at 1‐2 hours .…”
Section: Discussionmentioning
confidence: 99%
“…In adult studies, the maximum concentrations of MLT are reached with transdermal patches between 1 and 18 hours following application. [45][46][47][48][49]81 These human studies observed inconsistent concentrations of MLT between patches; generally, the higher dose patches showed a faster time to maximum concentration, for example 20-100 mg patches produced a peak circulation at 1-2 hours. 47 We undertook a small in vitro study to assess MLT release from the patches used in this study and found that MLT patches had a maximal diffusion rate of approximately 875 pg/mL/h (data not shown) reached at 2-4 hours, but this was highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…, Zetner et al . ). In the oral cavity, MEL exhibits paracrine effects on nearby cells, acting as an antioxidant and anti‐inflammatory molecule, proved to be useful in protecting dental and periodontal tissues and preventing bone resorption by acting via NF‐kB signalling (Cutando et al .…”
Section: Introductionmentioning
confidence: 97%
“…MEL can be administered by several routes (orally, intraperitoneally, or locally directly in the effect-site e.g. in dental implants) with a very wide safety margin (Cutando et al 2008, Zetner et al 2016. In the oral cavity, MEL exhibits paracrine effects on nearby cells, acting as an antioxidant and anti-inflammatory molecule, proved to be useful in protecting dental and periodontal tissues and preventing bone resorption by acting via NF-kB signalling (Cutando et al 2007, Calvo-Guirado et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Slow release, prolonged release, and surge sustained preparations are designed to extend the time of high circulating melatonin [18]. Melatonin has low bioavailability, in general, although it has been found that transmucosal administration increases bioavailability [19]. A critical feature of exogenous melatonin with regard to its clinical uses is its very low toxicity and lack of addictive properties [20,21].…”
Section: Melatonin As a Food Supplement And Its Uses In Modern Lifementioning
confidence: 99%